Effectiveness of Curcuma domestica leave extract in inhibiting the growth of Pseudomonas aeruginosa - Yuziani, Yuziani; Alvira, Mumtaz; Sahputri, Juwita (Narra Sains Indonesia, 2023)
Pseudomonas aeruginosa is one of the Gram-negative bacteria that causes nosocomial infection in patients admitted to the intensive care unit (ICU). The therapy provided could be antibiotics and the provision of therapy is considered difficult due to antibiotic resistance; therefore, an alternative is needed such as active ingredients from medicinal plants. Turmeric (Curcuma domestica) is believed to have compounds that have antibacterial activities. The aim of this study was to determine the antibacterial activities of ethanol extract from turmeric leaves against the growth of Pseudomonas aeruginosa. An experimental study was conducted using posttest-only design. Antibacterial activities were determined using disc diffusion method with concentration of 50%, 75%, and 100% Curcuma domestica extract. The positive and negative controls were ciprofloxacin and dimethyl sulfoxide (DMSO), respectively. The inhibition zone of 50%, 75%, and 100% extract groups against Pseudomonas aeruginosa were 8.9 mm, 10.6 mm, and 11.8 mm, respectively. There was no significant different of antibacterial activities between different concentrations of Curcuma domestica (50%, 75% and 100% of extracts). All groups of Curcuma domestica extract had lower antibacterial activities significantly than ciprofloxacin (positive control). This data indicated that the leave extract of Curcuma domestica had a weak inhibition against the growth of Pseudomonas aeruginosa.